Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Melalui Kepuasan Kerja Di The Meru Sanur Bali - Surya Nugraha; Ni Putu Widhya Pibriari Pibriari (Universitas Triatma Mulya, 2025)
This study aims to determine the effect of workload and work stress on performance through job satisfaction at The Meru Sanur Bali. The sampling method was carried out by proportional random sampling, where from 152 employees using the Lovin Husein Umar formula, (2003:108) 60 respondents were obtained where all respondents were given questionnaires randomly that the researcher met. The research data is secondary data obtained from The Meru Sanur Bali. The research hypothesis was tested using the Structural Equation Modeling (SEM) analysis technique with the Partial Least Square (PLS) approach. The results of the study showed that: (1) workload has a positive and significant effect on job satisfaction. (2) work stress has a positive and significant effect on job satisfaction. (3) workload has a positive and significant effect on performance. (4) work stress has a positive and significant effect on performance. (5) job satisfaction has a positive and significant effect on performance. (6) workload through job satisfaction has a positive and significant effect on performance. (7) work stress through job satisfaction has a positive and significant effect on performance. It is hoped that further research can examine other variables that influence employee job satisfaction.